Pengaruh Dukungan Sosial Guru dalam Memoderasi Hubungan Motivasi dan Passion Belajar Siswa Terhadap Student Engagement Mata Pelajaran Pjok di SMA Negeri 1 Randudongkal Kabupaten Pemalang - Muamar Muamar; Yohanes Suhari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aimed to examine and analyze the role of teacher social support in moderating the effect of motivation and passion on student engagement. The study population was students of SMAN 1 Randudongkal in Pemalang Regency, with 291 students as the sample determined by the Slovin formula. The research method used computer software with SPSS for Windows version 22. The data analysis method used Moderation Regression Analysis (MRA) with a quasi-moderator type. The results of the t-test significance obtained that the regression coefficient of the learning motivation variable was 0.190, and the significance was 0.001 (<0.05). The regression coefficient for the learning passion variable is 0.317 with a significance of 0.000 (<0.05), and the regression coefficient for the teacher social support variable is 0.343, and a significance of 0.000 (<0.05). From the results of this study, it can be interpreted that the teacher's social support, passion, and learning motivation positively affect student engagement. The interaction between learning motivation and teacher social support resulted in a regression coefficient of -0.031 and a significant 0.579 > 0.05. The results mean that teacher social support does not moderate the effect of learning motivation on student engagement. The interaction of passion-teacher social support resulted in a regression coefficient of 0.036 and a significant 0.518 > 0.05, meaning that teacher social support did not moderate the influence of learning passion on student engagement. In conclusion, teacher social support does not moderate the effect of student learning motivation on student engagement, and teacher social support does not moderate the effect of student learning passion on student engagement if, in practice, students have high motivation and passion for learning during the learning process. Keywords: motivation, teacher social support, passion, student engagement